Risk approach to supply chain management in the industrial sector - Uribe, Sophia Cristina (2022)
The purpose of the study was to provide a referential framework to manage risks in the supply chain through a bibliographic review, in such a way that the inherent risks in companies in the industrial sector can be reduced. The investigation was substantive to identify sources related to organizational risks and uncertainties were identified. Subsequently, a risk management approach is provided and subdivided into stages of risk identification, risk analysis; and risk control and monitoring. Among the techniques and instruments to manage risks, it is possible to use communication flows, the use of ERP system, and the method of association rules, among others.